Calculation of Temperature Fields in Multilayer Plates and Shells with Distributed Heat Sources - Smetankina, Natalia; Postnyi, Oleksii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The aircraft multilayer glazing is considered as a rectangular multilayer plate made up of isotropic layers with constant thickness. The temperature on the side surface of the plate is zero. Convective heat transfer occurs on outer surfaces of the plate; on layers' interfaces film heat sources are arranged. The heat conduction equation for an arbitrary plate layer is reduced to the functional equation. A solution of the functional equation we search in the form of three space functions product. We get the system of ordinary differential equations. Series expansion factors are determined from a system of linear algebraic equations. A transform of the required function is found by the second expansion theorem, and the problem solution has the form of double trigonometrical series. The comparative analysis of the results is carried out with the results of other method. The method offered can be used for designing a safe multilayer glazing under operational and emergency thermal and force loading in different vehicles.